2023
DOI: 10.3389/fitd.2023.1102265
|View full text |Cite
|
Sign up to set email alerts
|

Limited genetic variations of the Rh5-CyRPA-Ripr invasion complex in Plasmodium falciparum parasite population in selected malaria-endemic regions, Kenya

Abstract: The invasion of human erythrocytes by Plasmodium falciparum merozoites requires interaction between parasite ligands and host receptors. Interaction of PfRh5-CyRPA-Ripr protein complex with basigin, an erythrocyte surface receptor, via PfRh5 is essential for erythrocyte invasion. Antibodies raised against each antigen component of the complex have demonstrated erythrocyte invasion inhibition, making these proteins potential blood-stage vaccine candidates. Genetic polymorphisms present a significant challenge i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Previous studies have demonstrated significant antigenic variation in MSP-1 ( 11 13 ), and despite strong immunogenicity, this antigen failed to generate protection in Phase IIb studies ( 14 ). Rh5 has limited polymorphism in field isolates ( 15 , 16 ), is essential for erythrocyte invasion ( 17 ), anti-Rh5 blocks erythrocyte invasion ( 18 ), vaccination with Rh5 protects against P. falciparum challenge in non-human primates ( 19 ), and vaccination of humans results in a modestly reduced P. falciparum replication rate in controlled human challenge studies, but only at high anti-Rh5 concentrations ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated significant antigenic variation in MSP-1 ( 11 13 ), and despite strong immunogenicity, this antigen failed to generate protection in Phase IIb studies ( 14 ). Rh5 has limited polymorphism in field isolates ( 15 , 16 ), is essential for erythrocyte invasion ( 17 ), anti-Rh5 blocks erythrocyte invasion ( 18 ), vaccination with Rh5 protects against P. falciparum challenge in non-human primates ( 19 ), and vaccination of humans results in a modestly reduced P. falciparum replication rate in controlled human challenge studies, but only at high anti-Rh5 concentrations ( 20 ).…”
Section: Introductionmentioning
confidence: 99%